Supply chain integration, strategic choice and corporate growth of agricultural companies: an analysis of dynamic QCA - Fan, Xiaonan; Wang, Ye; Jiang, Huiling (Frontiers in Sustainable Food Systems, 2025)
The corporate growth is an important measure of the sustainable growth ability. Most of the existing literature discusses the influence of single factor on the corporate growth. Based on the match of strategy and structure, this research discusses the configuration effects of supply chain integration and strategic choice on the corporate growth of agricultural companies by using dynamic QCA. The main findings are as follows: (1) The match of structure and strategy can better explain high corporate growth, but a single factor does not constitute the necessary condition for high corporate growth. The necessity of the same group effect has time effect. (2) There are three configurations promoting the high corporate growth, which are Internal Collaboration-Imitation Driven Type, Internal Collaboration- Innovation Driven Type, Internal and External Integration-Innovation Driven Type. (3) The Between results show that the consistency of configuration 1 increases in 2020, while the consistency of configuration 2 and configuration 3 decreases. The Within results show that the collaboration between internal integration and peer effect can better explain the high corporate growth of state-owned companies. The collaboration of internal integration, customer integration, and entrepreneurial orientation can better explain the high corporate growth of private companies. (4) At the structure level, agricultural companies do not need to focus on supplier integration. The coordination of internal and external integration is an important condition for the development of companies, among which internal integration is the most important. At the strategy level, entrepreneurial orientation is crucial for the corporate growth. (5) There is a substitution relationship between the factors. When internal integration exists, the peer effect and entrepreneurial orientation can replace each other. The research makes up for the shortcomings of existing research on agricultural supply chain, and provides reference for the sustainable growth of agricultural companies.